DIPLOMASI BUDAYA INDONESIA DALAM KEJUARAAN SEPEDA INTERNASIONAL (TOUR DE IJEN) DI BAYUWANGI - Lubis, M. Rizki Dailami; Tjarsono, Idjang (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
This study analyzes of how Tour de Ijen in cooperation with the UCI (Union Cycliste Internationale / International Cycling Union) can increase tourism and economic development in Banyuwangi. Tour de Ijen is the official cycling championships of the UCI (Union Cycliste International) which is held every year in Banyuwangi . Championship was first held in 2012. This is a long-distance road racing is generally held around November to December and lasts for 4 days . Tour De Ijen is as a means of publicity and promotion (media campaign) Banyuwangi to national, regional and international levels. Banyuwangi can be known with all its potential so as to encourage as a tourist destination and the purpose of investment, domestic investment and foreign investment .Keywords : Cultural Diplomacy, Tour de Ijen, Banyuwangi, UCI